Non-cell autonomous neuroprotective effect of carbon monoxide : microglia-to-neuron communication - Soares, Nuno Ricardo Lucas (2017)
RESUMO: A isquémia cerebral é uma das doenças mais predominantes a nivel mundial, sendo uma das principais causas de mortalidade e invalidez. Parte da propagação de dano no cérebro é causado por inflamação descontrolada, causada principalmente por disfunção da microglia. Desta forma, existe a necessidade de tentar desenvolver estratégias para melhor compreender e modular as acções destas células. O monóxido de carbono (CO), é uma molécula endógena com provas dadas como anti-neuroinflamatório em vários modelos. Assim, o principal objectivo do trabalho foi o estudo do CO como um modulador da acção da microglia, com principal foco dado à comunicação entre estas células e neurónios, tentando entender se existe um efeito neuroprotector por inibição da inflamação. Um protocolo de meio condicionado foi estabelecido usando as linhas celulares BV2 e SH-SY5Y, de microglia e neurónio. A molécula CORM-A1, que liberta expontaniamente CO, foi usada como método de entrega da molécula às celulas. Demonstrámos que o pre-tratamento de células BV2 com CORM-A1 gera neuroprotecção já que reduz a morte celular de neurónios SH-SY5Y quando são incubados com meio condicionado de microglia activada em conjunto com o pró-oxidante t-BHP (tert-butil hidroperóxido). Assim, considerámos que o CO promove neuroprotecção ao inibir as acções inflamatórias da microglia. O papel anti-inflamatório da molécula CORM-A1 foi confirmado quando se verificou que pré-tratamento desta molécula em microglia BV2 limita a secreção de TNF-α mas estimula a secreção de IL-10. Por último, a CORM-A1 induziu a expressão do receptor da microglia CD200R1, molécula que participa na comunicação neurónio-microglia e fundamental para a modulação das acções inflamatórias destas últimas. Em suma, o nosso trabalho reforçou as propriedades anti-neuroinflamatórias do CO e uma capacidade de modular viabilidade neuronal através do seu efeito a nível de comunicação célula-célula. ---------------------------- ABSTRACT: Brain ischemia is a widespread disease worldwide, being one of the main causes of mortality and permanent disability. A portion of the damage that ensues following the ischemic event is caused by unrestrained inflammation, which is mainly orchestrated by exacerbated microglial activity. Hence, developing strategies for modulating microglial inflammation is a major concern nowadays. The endogenous molecule carbon monoxide (CO) has been shown to possess anti-neuroinflammatory properties using in vitro and in vivo approaches. Thus, our objective was to study CO as modulator of microglial activity, in particular in what concerns their communication with neurons, by promoting neuronal viability and limiting inflammatory output of activated microglia. A conditioned media strategy was established with BV2 microglia and SH-SY5Y neurons as cell models. CO-releasing molecule A1 (CORM-A1), a compound that releases CO spontaneously, was used as method of CO delivery to cells. We found that CORM-A1 pre-treatment in BV2 cells yields neuroprotective results, as it limits cell death when SH-SY5Y neurons are challenged with conditioned media from LPS-activated microglia and the pro-oxidant t-BHP (tert-butyl-hydroperoxide). Thus, we assumed carbon monoxide promotes neuroprotection via inhibition of microglial inflammation, displaying a non-cell autonomous role. CORM-A1 pre-treatment limited inflammation by inhibiting BV2 secretion of TNF-α and stimulating IL-10 production. These results reinforce that CO’s anti-inflammatory role confers neuroprotection, as the alterations in these cytokines occur concurrently with the increase in SH-SY5Y viability. Finally, we showed for the first time that carbon monoxide promotes the expression of CD200R1, a microglial receptor involved in neuron-glia communication and modulation of microglia inflammation. Further studies are necessary to clarify this role. Altogether, other than just highlighting CO as an anti-inflammatory and neuroprotective molecule, this work set the foundation for disclosing its involvement in cell-to-cell communication.